2021
DOI: 10.1016/j.jsps.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Gastric floating tablet improves the bioavailability and reduces the hypokalemia effect of gossypol in vivo

Abstract: Gossypol (Gos) is a natural polyphenolic compound that has shown a number of valuable biological properties such as antifertility, antioxidation, and antitumor activities. However, the clinical application of Gos has been hindered by its notable adverse effects such as hypokalemia, hemolytic anemia, and so on. Using sustained-release dosage form provides a hopeful solution to this problem. In this study, a gastric floating tablet for sustained-release of Gos (Gos-GFT) was developed using polyvinylpyrrolidone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The body weight loss of the mice may indicate the potential systemic toxicity and adverse effects of the drug. 2 , 39 As shown in Figure 9D , within the dose schedule adopted for each group in this study, no significant change in the body weight was observed throughout the experiment. Among the five groups, the free (-)-gossypol group showed the largest body weight loss of 4.36% at the end of the experiment, as compared with the average body weight on day 1, which may indicate slight systemic toxicity of the orally administered free drug.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The body weight loss of the mice may indicate the potential systemic toxicity and adverse effects of the drug. 2 , 39 As shown in Figure 9D , within the dose schedule adopted for each group in this study, no significant change in the body weight was observed throughout the experiment. Among the five groups, the free (-)-gossypol group showed the largest body weight loss of 4.36% at the end of the experiment, as compared with the average body weight on day 1, which may indicate slight systemic toxicity of the orally administered free drug.…”
Section: Resultsmentioning
confidence: 77%
“…Hypokalemia is a major adverse effect of gossypol (including its racemate and (-)-gossypol) that may happen after repeated/long-term treatments, which is related to the impacts of the drug on the renal tubules. 2 Therefore, monitoring the plasma K + level is a need for the safety of repeated/long-term use of gossypol. In this study, cRGD peptide with high affinity to α v β 3 integrin was incorporated into the liposome for enhanced tumor-targeted delivery of (-)-gossypol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations